Penataan Administrasi Desa, Kesadaran Hukum, Pemberdayaan UMKM, dan Inovasi Pembelajaran Desa Mojokumpul Kecamatan Kemlagi Mojokerto - Dadang Purwoari Widodo; Moch. Fachur Rochman; Dhorrotun Nafisa; Lujeng Lutviyah; Miftakhul Jannah; Muhammad Ali Ridwan Junaedi; Yovina Maylanda Cristanti; Kevin Putra Agustin; Muhammad Rizaldi Febriyan Amri; Titi Maimunah; Titania Nur Isnaini; Romadhoni Romadhoni; Setya Budi Anaggara; Deryl Misbakhul Rizat; Kennyalia Twist Leksono; Kiki Putri Yuanastiti; Leynisstyawan Octavi; Diajeng Gayatri; Aditia Dwi Riswanto; Mokhammad Sulthon Hisam; Aprillia Ayu Devina Ranti; Muhammad Naufal Hanan; Achmad Rahul Ashari; Christian Yulianto H (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Counseling, Mentoring and Empowerment are activities to increase community participation in meeting life's needs to resolve problems experienced by the community. Activities are carried out through the Real Work Lecture (KKN) program, which is a community service-based activity to increase student empathy for the conditions of society and the environment. Science KKN is carried out in Kemlagi District, Mojokerto Regency using service methods such as counseling, training and group mentoring. The results show that there is a positive response from village stakeholders and high active participation from the community, including taking part in an extension program with four activities, namely structuring Village Administration, Legal Awareness, Empowering MSMEs, and Learning Innovation. Apart from that, there are several outputs produced: (1) Strengthening data recording, archiving and reporting Village finances correctly (2) Increasing order, peace, security and justice in Village social life (3) Development of quality, competitiveness and added value of production home and halal certification (4) There has been an increase in discipline and participation in the teaching and learning process in an orderly and structured manner.